Penerapan Model Pembelajaran Kooperatif Tipe STAD Dengan Teknik Jari Sakti Untuk Meningkatkan Hasil Belajar Matematika - Awaludin, Asep (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2020)
The low results of mathematics learning achieved by grade VI students of SD N Pamedaran 01. This is due to the low ability of students in multiplication mastery. Therefore, the purpose of the problem raised in this study is "Is it with the application of cooferative learning model type STAD with Jari Sakti technique, the results of mathematics learning in grade VI SD N Pamedaran 01 can be improved?" The research was conducted in two cycles, consisting of four stages, namely planning, implementation, observation, and reflection. the learning outcomes achieved in cycle I scored an average of 69.26 and classically completed 62.96%, students who scored ≥70 were 17 students. In cycle II student learning outcomes increased with an average score of 75.19 and a classical study completion of 81.48, students who scored ≥70 were 22 students.  It was concluded that with the application of cooperative model type STAD with Jari Sakti, the results of learning mathematics in grade VI SD N Pamedaran 01 can be upgraded.